Peran Penanaman Pohon dalam Pelestarian Lingkungan dan Pengembangan Ekonomi Masyarakat Desa Sekitar Tahura Gunung Palasari - Wahyuni, Dwi; Wilujeng, Sri; Darliana, Ina; Srimulyaningsih, Reni; Tanjung, Ishak (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
The forest area that plays a role in conservation efforts in Sumedang is the Gunung Palasari Grand Forest Park (TAHURA). These efforts can fail with various threats such as deforestation, exploitation and even economic pressure on the community that puts the condition of the area in a critical situation. The stages of prevention of this threat involve collaboration from various parties, such as academics, the community, and various other stakeholders. The purpose of this study is to invite the community and its surroundings to know the role of trees and want to play a role in planting trees for environmental conservation and developing the community's economy. The academics who contributed were the Faculty of Forestry, Winaya Mukti University, who took an approach through the seminar lecture method. The seminar was held on November 29, 2024 from 08.00 - 16.00 at TAHURA Gunung Palasari which was divided into three sessions, namely material presentation, discussion and tree planting. The material presented was targeted to gain community knowledge about plants, especially trees and their benefits, as well as public awareness to understand the importance of planting trees. This activity was declared successful in achieving its target based on the N-gain test, which obtained 60% from the difference in each pre-test to post-test parameter. The suggestion from this research is that routine planting activities should continue to be carried out.